Gender operationalisation and stress measurement in research with adolescent males: a scoping review - Parise Carmichael-Murphy; Ola Demkowicz; Neil Humphrey (BMC, 2022)
Abstract Aim Stress measurement in adolescent males is in its relative infancy, which is likely to influence the effectiveness of mental health services for this heterogeneous population. Although evidence suggests the prevalence of mental health difficulties increases during adolescence, the relationship between gender and stress measurement is less explored or understood. This review summarizes findings on gender operationalisation and stress measurement in research with adolescent males. Methods For this scoping review, six electronic databases across social and life sciences were searched using terms linked to adolescence, male, stress and research design. Articles were screened, data were extracted, and a narrative synthesis used to characterise studies by research design, adaptation of method for participants' cultural context, operationalisation of gender, and measurement of stress. Results Searches identified 3259 citations, 95 met inclusion criteria and were reviewed. Findings suggest that research on psychological stress in adolescence is a developing field, but one that is currently dominated by Western studies. Furthermore, the results indicate that stress measurement research with adolescent males tends not to make adaptations relative to participants' gender, age, or context. Conclusions Stress research with adolescent males is lacking in scope. This review highlights the need for researchers to consider stress responses as more than a biological response, as it has been conceptualised historically. Recommendations for researchers to report research design and protocol more clearly are made to support readers to understand how stress and gender have been operationalised and measured and how this may influence research methodology. Future research should avoid conflating biological differences with gendered experience and demonstrate greater sensitivity to how gender identity may intersect with age and location to perpetuate gendered inequalities.